ANALISIS FAKTOR PEMBULLYAN VERBAL DI LINGKUNGAN SEKOLAH TERHADAP ETIKA BERKOMUNIKASI DAN SOLUSI PENDIDIKAN ISLAM - Muhammad Hanif Fadhillah; Siti Tasliyah, Alifahtul Zahro, Dimas Surya Bekti Utama (ADISAM PUBLISHER, 2024)
This study aims to analyze the factors causing verbal bullying at SMPN X in Jakarta and their effects, as well as to examine solutions and the role of Islamic education in addressing verbal bullying cases at SMPN X in Jakarta. This research employs a mixed-method approach, with data collected through in-depth interviews with religion teachers and school counselors, as well as questionnaires completed by students. The collected data is then analyzed comprehensively to identify patterns, themes, and relevant factors. The findings reveal three main factors contributing to verbal bullying: peer influence, family background, and social media. However, these three factors do not significantly affect students' communication ethics